2003
DOI: 10.1103/physrevd.67.056001
|View full text |Cite
|
Sign up to set email alerts
|

CPviolation in hyperon nonleptonic decays within the standard model

Abstract: We calculate the CP -violating asymmetries A(Λ 0 − ) and A(Ξ − − ) in nonleptonic hyperon decay within the Standard Model using the framework of heavy-baryon chiral perturbation theory (χPT). We identify those terms that correspond to previous calculations and discover several errors in the existing literature. We present a new result for the lowest-order (in χPT) contribution of the penguin operator to these asymmetries, as well as an estimate for the uncertainty of our result that is based on the calculation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 51 publications
6
68
0
Order By: Relevance
“…Hyperon semileptonic and radiative decay are still a challenge on both experimental and theoretical fronts. The rare and forbidden hyperon decays will play important role in the search for new physics [3,[71][72][73][74][75][76][77][78][79][80][81][82]. In this paper, we propose studying hyperon decays at BE-SIII with events in the J/ψ or ψ(2S) decay into hyperon pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperon semileptonic and radiative decay are still a challenge on both experimental and theoretical fronts. The rare and forbidden hyperon decays will play important role in the search for new physics [3,[71][72][73][74][75][76][77][78][79][80][81][82]. In this paper, we propose studying hyperon decays at BE-SIII with events in the J/ψ or ψ(2S) decay into hyperon pairs.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the corresponding baryonic operator that triggers the nonleptonic hyperon decay is given by [36]:…”
Section: Although Numerous Beyond Standard Model (Bsm) Scenarios Havementioning
confidence: 99%
“…These phases have been considered in ref [15], but their treatments are less satisfactory due to the neglect of the operator mixing effect and a certain outdated approximation of the small top quark mass assumption. In order to improve upon that, I review a more recent work done in ref [36] that determined {ϕ D , ϕ F } and apply scaling arguments to provide an estimate of {φ D ,φ F }. Ref [36] pointed out that after considering operator mixing and renormalization group running, the dominant operator that gives rise to the CP-violating phase in the |∆S| = 1, |∆I| = 1/2 sector is given by:…”
Section: Determination Of the Lecsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard model prediction for A(Λ 0 − ) is around 3 × 10 −5 , and the recent study in Ref. [2] showsA model independent study of new CP −violating interactions has shown that A(Λ 0 − ) could be larger than that predicted within the standard model [6]. An example of an operator is precisely the gluonic dipole operator [1,6], in which A(Λ 0 − ) would be enhanced and could reach around O(10 −3 ) [1].…”
mentioning
confidence: 67%